A Scientific Literacy Model Integrated with Islamic Values through Technology Project-Based Learning - Eni Fariyatul Fahyuni; Nuril Huda; Muhajir (International Journal on Integrated Education, 2026)
This study aims to analyze the effectiveness of a scientific literacy learning environment model integrated with Islamic values through the Technology Project-Based Learning (TPjBL) approach in improving the scientific literacy of SMP/MTs students. This research employed a quantitative approach using a quasi-experimental pretest-posttest control group design. The research subjects consisted of 68 students divided into an experimental group of 34 students and control group of 34 students. The experimental group received treatment through the TPjBL model integrated with the values of amanah, ihsan, and khalifah, while the control group received conventional instruction previously implemented by the science teacher in collaboration with the Islamic education teacher. The research instrument was a scientific literacy test with scores ranging from 0 to 100. The data were analyzed using the Shapiro-Wilk normality test, Levene’s homogeneity test, paired-samples t-test, independent-samples t-test, and N-Gain analysis. The results showed that the mean score of the experimental group increased from 55.87 in the pretest to 87.42 in the posttest, with an N-Gain score of 0.62 in the moderate category. Meanwhile, the control group increased from 55.16 to 66.94, with an N-Gain score of 0.27 in the low category. The independent-samples t-test revealed significant differences between the experimental and control groups in posttest scores (t = 6.879; p < 0.001) and N-Gain scores (t = 10.014; p < 0.001). These findings indicate that the scientific literacy learning environment model integrated with Islamic values through the TPjBL approach is more effective than conventional instruction. This model not only improves students’ scientific literacy but also strengthens their engagement in real-world projects, data use, collaboration, reflection, and the internalization of Islamic values in science learning.